Lean Practices in the Process of New Product Development: Case of Study in a Food Industry Cooperative in Brazil - Zamin, Simone; Nichetti, Leandro José; Cescon, José Antonio; Martins, Vinícius Abílio; Lima, Nilton César (Journal of Agricultural Studies, 2021)
This article presents a case study of employees’ perception of Lean Manufacturing in the development process of new products at a Food Industry Cooperative in Brazil. A survey was applied in all areas of the company to measure the perception and understanding of employees regarding Lean Management and Lean Thinking. Also, to understand their knowledge of the principles and practices in developing new products in the company. The results showed that 76% of the responding employees have some understanding of lean management. It also shows low engagement by stakeholders and the board in the new product development process stages and weak integration between areas, such as environmental, engineering, and finance. On the other hand, RD& area presented higher engagement, with 90% of its staff supporting this process.